Pencegahan Penyalahgunaan Peredaran Narkoba di Ditnarkoba Polda Gorontalo - Rivaldy K. Husain; Yacob Noho Nani; Rusli Isa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the prevention and control of illicit drug trafficking within the Narcotics Directorate of the Gorontalo Regional Police (Ditnarkoba Polda Gorontalo) in accordance with public service standards, particularly in terms of service delivery and management. The study employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and document analysis. The informants consisted of the Director of the Narcotics Directorate, investigators, internal personnel, and service recipients. Data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing. This research is important because drug prevention services are not only related to law enforcement but also involve community protection, public education, and strengthening public trust in police institutions. The findings show that service delivery in the prevention and control of illicit drug trafficking has not been optimal. This is indicated by limited dissemination of information regarding service requirements, procedures, completion time, service fees, service products, and complaint channels, which are not yet fully communicated in an open and accessible manner. Although reporting services, information reception, and public outreach activities have been implemented, many community members still depend on direct explanations from officers. Furthermore, service management has not been fully optimized, as legal foundations, standard operating procedures, facilities, personnel competencies, supervision, service guarantees, and performance evaluation systems are not yet integrated into a transparent and responsive governance system. This study recommends strengthening information systems, service procedures, communication skills, and community satisfaction surveys.